Rapid sequence intubation in the emergency department: 5 year trends. Issue 1 (22nd December 2005) - Simpson, J; Munro, P T; Graham, C A
Abstract : Aim: Airway management is a core aspect of emergency medicine. The technique of rapid sequence intubation (RSI) creates continuing debate between anaesthetists and emergency physicians in the UK, although similar complication rates for emergency department (ED) RSI have been shown for both specialties. This study examined prospectively collected data on every ED RSI performed in a university hospital in Glasgow over 5 years. Methods: Data were prospectively recorded for every attempted RSI in the ED on a dedicated form (as used in previous studies) between January 1999 and December 2003. Immediate complications were specifically sought in the questionnaire, as was the immediate destination on leaving the ED. The χ 2 test was used for categorical data. Results: On average, 51 ED RSI were performed annually (range 42–60). Emergency physician RSI for trauma increased from 32% (7/22) in 1999 to 75% (21/28) in 2003 (χ 2  = 9.32, df = 1, p = 0.002) and for non-trauma from 62% (18/29) in 1999 to 79% (23/29) in 2003 (χ 2  = 2.08, df = 1, p = 0.15). Complication rates for emergency physician RSI decreased from 43% (3/7) to 14% (3/21) for trauma (χ 2  = 2.55, df = 1, p = 0.11) and from 28% (5/18) to 4% (1/23) for non-trauma (χ 2  = 4.44, df = 1, p = 0.035). This compares with mean complication rates for anaesthetists for trauma of 17% and for non-trauma of 22%. Incidence of hypotension decreased in all groups; however, oxygen desaturation is now the most common complication. The rate of ED RSI prior to computed tomography (CT) scans increased in both the trauma (79% v 42%; χ 2  = 7.42, df = 1, p = 0.0065) and non-trauma (48% v 17%; χ 2  = 5.85, df = 1, p = 0.016) groups. Conclusion: Emergency physician performed ED RSI is increasingly common but is not associated with overall higher numbers of RSIs being performed in the ED. Effective pre-oxygenation should be emphasised during training.